Development and Characterization of Catechin-Loaded Self-Nanoemulsifying Drug Delivery System: Pharmacokinetics, Toxicity Assessment, and in vivo Anti-Ulcer Activity Evaluation - Pathak, Rashmi; Chandra, Phool (Indian Journal of Pharmaceutical Education and Research, 2026)
Purpose: This research aimed to prepare catechin-loaded SNEDDS that would improve the oral therapeutic efficacy of catechin. Materials and Methods: Catechin-SNEDDS was prepared and characterized using emulsification time, percent transmittance, thermodynamic stability, droplet size, polydispersity index, and morphological characterization. Tween 80 (surfactant), propylene glycol (co-surfactant), and olive oil (oil phase) with the highest solubility of catechin were used to prepare catechin-SNEDDS. Out of two catechin-SNEDDS (ME2F1 and ME2F2), ME2F2 passed the thermostability test and was further tested. Results: The obtained ME2F2 had a droplet size <100 nm, percent transmittance 99.60±0.01%, emulsification time 10s, PDI 0.232, and was morphologically spherical. Further evaluations showed that ME2F2 has no toxicity, and pharmacokinetic study showed the AUC0-t is 1.65 µg/mL*h for catechin and 2.14 µg/mL*h for ME2F2. As a result, higher Cmax and AUC for ME2F2 in comparison to catechin are evidence of improved systemic drug absorption, which increases oral bioavailability. Further in vivo anti-ulcer activity showed that ME2F2 reduces the formation of ulcers, gastric juice volume, ulcer index, and increases pH in comparison to the ulcer control group. Histopathological estimation of stomach ulcers showed a reduction in ulcer and inflammation in the gastric layer in the ME2F2 treated group. In vivo antioxidant activity on stomach tissue for ME2F2 showed an increase in CAT, SOD, and GSH levels in response to oxidative stress and a decrease in LPO levels, indicating the formulation’s antioxidant activity. Conclusion: Catechin's gastroprotective properties and anti-oxidative efficacy are improved by SNEDDS. According to research, it has a good probability of becoming a bioactive substance used as an anti-ulcer agent.
Keywords: Catechin; SNEDDs; Bioavailability; Anti-ulcer; Anti-oxidant.